2013
DOI: 10.2134/jeq2013.03.0101
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Assessment of the Beef Cattle Production System for the Northern Great Plains, USA

Abstract: A life‐cycle assessment (LCA) model was developed to estimate the environmental impacts associated with four different U.S. Northern Great Plains (NPG) beef production systems. The LCA model followed a “cradle‐to‐gate” approach and incorporated all major unit processes, including mineral supplement production. Four distinct operation scenarios were modeled based on production strategies common to the NGP, and a variety of impacts were determined. The scenarios include a normal operation, early weaning of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 33 publications
4
44
5
Order By: Relevance
“…This is contrary to many commonly reported LCA analyses indicating that cow-calf enterprises account for the highest GHG emission in the beef production [11], which is misleading as most of these analyses do not consider the GHG sequestration in the ecosystem being studied. In addition, these analyses do not consider the GHG emissions generated by cropping practices [45,49] and soil erosion [50] associated with grains fed during the non-grazing portions of the production cycle.…”
Section: Carbon Sequestrationcontrasting
confidence: 86%
See 2 more Smart Citations
“…This is contrary to many commonly reported LCA analyses indicating that cow-calf enterprises account for the highest GHG emission in the beef production [11], which is misleading as most of these analyses do not consider the GHG sequestration in the ecosystem being studied. In addition, these analyses do not consider the GHG emissions generated by cropping practices [45,49] and soil erosion [50] associated with grains fed during the non-grazing portions of the production cycle.…”
Section: Carbon Sequestrationcontrasting
confidence: 86%
“…Cattle transportation from the site of cow-calf production to the next phase of production is not considered. The functional unit, to which all the environmental loads in the LCA are related, is generally defined as 1 kg live or carcass weight if the entire beef production systems are studied, which includes cow-calf, backgrounding and finishing systems [11]. As the boundary of our LCA study is limited to the calf-cow production system, we define the functional unit as one marketed beef calf as in Ogino et al [16], so that our result can be easily compared with literature value from other regions.…”
Section: The Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The backgrounding phase in the beef production system (cow (calf through to feedlot) may make a significant contribution to net whole-farm GHG emissions. Using life-cycle assessment for the US beef production systems, Pelletier et al (2010) and Lupo et al (2013) reported that the backgrounding systems contributed 8 to 20% of the total net whole-farm GHG emissions of the beef production system, i.e., cowÁcalf through to feedlot.…”
Section: Results and Discussion System Boundariesmentioning
confidence: 99%
“…However, the greater estimates using CCM (77%) can be attributed to the greater emission factor used in COWPOLL (7-8% of gross energy intake) than the default IPCC value (6% of gross energy intake) used in the previous studies. In a cow-calf backgrounding production system, Pelletier et al (2010) and Lupo et al (2013) reported that beef cows and backgrounded animals contributed 68-81% and 11-24% of the total farm GHG emissions, respectively. Furthermore, Beauchemin et al (2010) indicated that beef cows and backgrounded animals contributed up to 79% and 7%, respectively, of farm CH 4 emissions from enteric fermentation.…”
Section: Baseline Scenariomentioning
confidence: 99%